2023
DOI: 10.1029/2022jd038012
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Burning Is a Non‐Negligible Source for Ammonium During Winter Haze Episodes in Rural North China: Evidence From High Time Resolution 15N‐Stable Isotope

Abstract: The refined source apportionment of ammonium (NH4+), especially for biomass burning emissions, is unclear. Hourly resolution δ15N‐NH4+ values for three winter haze episodes (EP1–EP3) were determined in the North China Plain (NCP) in 2019 to identify and quantify the contribution of biomass burning. A reasonable source‐resolved structure of NH4+ was obtained after using the corrected source signatures of 15N and considering biomass burning emissions. The time‐series variation in biomass burning and vehicle sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Therefore, more attention should be paid to SO 2 emissions from traffic and biomass burning in Hebei Province. Compared with EP1, the contributions of biomass burning in EP2 and EP3 were 16% and 13% respectively, which were attributed to the air mass trajectory passing through a relatively sparse number of fire points in this region (Fire Information for Resource Management System, https://firms.modaps.eosdis.nasa.gov/map) (Feng et al., 2023). The coal combustion contributions to SO 4 2− in EP2 and EP3 were significantly higher than those of EP1, accounting for 51% and 62%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more attention should be paid to SO 2 emissions from traffic and biomass burning in Hebei Province. Compared with EP1, the contributions of biomass burning in EP2 and EP3 were 16% and 13% respectively, which were attributed to the air mass trajectory passing through a relatively sparse number of fire points in this region (Fire Information for Resource Management System, https://firms.modaps.eosdis.nasa.gov/map) (Feng et al., 2023). The coal combustion contributions to SO 4 2− in EP2 and EP3 were significantly higher than those of EP1, accounting for 51% and 62%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure S3, the concentration of OC exhibited good correlations with the concentration of EC ( r 2 = 0.70, p < 0.01) and nonsea-salt Cl – (nss-Cl – , r 2 = 0.55, p < 0.01), respectively, However, weak correlations were observed between OC and monosaccharides ( r 2 = 0.1–0.3, p < 0.01). nss-Cl – is commonly used as an indicator of coal combustion , ; nevertheless, many studies have suggested that Cl – may also come from biomass and other combustion processes. , As indicated by our recent work, a relatively minor contribution of biomass burning to particulate pollution was found during the sampling campaign, , and nss-Cl – showed insignificant correlations with monosaccharides, probably suggesting that nss-Cl – was less affected by biomass burning in this study. Residential coal combustion is commonly adopted for winter heating and has been identified as the main source of anthropogenic pollution. , Additionally, the results obtained through 14 C analysis revealed that fossil sources contributed more than 50% of the total OC during the sampling campaign.…”
Section: Resultsmentioning
confidence: 39%
“…nss-Cl − is commonly used as an indicator of coal combustion 43,44 ; nevertheless, many studies have suggested that Cl − may also come from biomass and other combustion processes. 45,46 As indicated by our recent work, a relatively minor contribution of biomass burning to particulate pollution was found during the sampling campaign, 47,48 and nss-Cl − showed insignificant correlations with monosaccharides, probably suggesting that nss-Cl − was less affected by biomass burning in this study. Residential coal combustion is commonly adopted for winter heating and has been identified as the main source of anthropogenic pollution.…”
Section: The Importance Of Nocs On Particulatementioning
confidence: 96%
“…A 30 cm 2 filter membrane was extracted with 20 mL of Milli-Q water for 30 min. The concentrations of water-soluble ions (Na + , K + , Ca 2+ , Mg 2+ , Cl – , NO 3 – , SO 4 2– , and NH 4 + ) were measured using an ion chromatograph (ICS 6000, Thermo Fisher, USA). , The dual oxygen isotopes (δ 18 O and Δ 17 O) were determined after converting NO 3 – (0.8 μgN) to N 2 O through denitrification bacteria (ATCC13985) . The N 2 O gas is catalytically decomposed to N 2 and O 2 by placing it in a gold tube at 800 °C .…”
Section: Methodsmentioning
confidence: 99%
“…Meteorological parameters such as temperature (T), humidity (RH), wind speed (WS), and pollutant concentrations, including PM 2.5 , SO , and NH 4 + ) were measured using an ion chromatograph (ICS 6000, Thermo Fisher, USA). 24,25 The dual oxygen isotopes (δ 18 O and Δ 17 O) were determined after converting NO 3 − (0.8 μgN) to N 2 O through denitrification bacteria (ATCC13985). 26 The N 2 O gas is catalytically decomposed to N 2 and O 2 by placing it in a gold tube at 800 °C.…”
Section: Sample Collectionmentioning
confidence: 99%